Design and validation of an observation instrument to assess decision making in the block action of volleyball - Conejero Suárez, M.; Prado Serenini, A. L.; Claver Rabaz, F.; González-Silva, J.; Moreno Arroyo, M. P. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2018)
The main aim of study was to design and validate an observational instrument to measure decision-making in the block action of volleyball players in formative stages. The instrument is an adaptation of the GPAI (Oslin, Mitchell, & Griffin, 1998) in which were included the criteria for evaluating decision-making (appropriate or inappropriate) in the action of block. Initially, in the design process, a literature review was conducted to establish the criteria for the observation. Content validity was established on a qualitative level (understanding, reading and relevance of the questions) and quantitative level (global rating scale from 0 to 10), through the agreement and consensus of thirteen experts judges. All items of the final instrument had a rating above .67 in the Aiken`s V coefficient. The instrument developed in this study has content validity to evaluate the decision-making in the block action in volleyball training stages.